Sea level changes and conodont correlation across the Iapetus Ocean during the Late Tremadocian - Early Arenigian. - BAGNOLI, GABRIELLA (1994)
In the Lower Ordovician platform and slope deposits of western Newfoundland and in platform deposits of Oeland (Sweden) transgressive-regressive cycles of the third order, superimposed to the global Cambro-Ordovician sea level rise have been recognized. Conodont faunas from the Newfoundland slope deposits allow correlation between Laurentia and Baltica across the Iapetus Ocean. Four transgressive-regressive cycles have been recognized